Development and validation of an assessment tool for public perceptions toward drive-thru community pharmacy services in Malaysia during COVID-19 - Ababneh, Bayan Faisal; Ong, Siew Chin; Alsaloumi, Louai; Hussain, Rabia (Frontiers in Public Health, 2023)
Introduction Community pharmacists' roles have expanded and undergone a significant transition over the last few years. Consequently, new and different pharmacy services, such as drive-thru pharmacy services, have emerged. Drive-thru pharmacy services began three decades ago and continued even during outbreaks such as the COVID-19 pandemic. Patients' perceptions are essential to the successful implementation and satisfaction with any new service. This study examines the reliability and validity of the assessment tool of public perceptions toward drive-thru community pharmacy services in Malaysia during COVID-19. Methods A cross-sectional study was conducted. The developed tool consists of 28 items to evaluate believed advantages toward drive-thru community pharmacy services, believed disadvantages toward drive-thru community pharmacy services, differences between drive-thru community pharmacy services and instore drug refill services, perceptions toward drive-thru community pharmacy services and feelings regarding how the introduction of drive-thru pharmacy services may affect the image of community pharmacists. Exploratory factor analysis (EFA) was performed to identify the factors of the developed tool, and confirmatory factor analysis (CFA) evaluated the model fitness. Results The EFA identified five elements and 25 items for the tool, and through CFA results, the observed model of the 25 items structure of the tool was verified as an excellent fit for the data [χ2 (265, N = 565) = 819.586, p < 0.001, IFI = 0.931, CFI = 0.93, RMSEA = 0.064]. The results of the CFA indicated a good model fit between the observed model and the proposed model. The internal reliability of the entire tool and each factor was very satisfactory as Cronbach's Alpha for the whole structured tool was 0.843 and for each factor was as follows, first factor (believed advantages) = 0.909, second factor (believed disadvantages) = 0.921, third factor (differences between drive-thru and instore refill) = 0.647, fourth factor (perceptions) = 0.926, and fifth factor (feelings) = 0.681. Conclusion The developed and validated tool would be valuable for assessing the public's perceptions of the drive-thru community pharmacy service during COVID-19 and future pandemics.